Supply Chain Management and Organization Performance: A Value Creation Perspective - Kyeremeh, Evans; Dza, Mawuko (Archives of Business Research, 2018)
The purpose of the study is to investigate how manufacturing firms in Ghana create value along the supply chain by integrating their unique skill-sets and building strong relationships among partners of the chain. The key objective is to examine how strategic supply chain management practices improve organisations performance. Data were collected and analyzed using exploratory factor analysis, correlation, regression analysis and other analytic techniques. The findings revealed that although supply chain management practices have some level of impact on supply chain performance, the effect is less influenced by value creation. With a β =.568; t=5.316, the implication is that there is about 53% change in supply chain performance when a single value is created. However, value creation does not perfectly moderate supply chain management practices. Additionally, the study shows that value creation influences information and technology management to significantly contribute negatively on supply chain performance by about 26% (β =-0.26; t=-2.226). It is therefore imperative for practitioners in the manufacturing sector to identify key supply chain management practices, which greatly impact on supply chain performance in order to optimize production.